Assessment of heavy metals in water, fish tissues and soil from selected fish farms in Ekiti State, Nigeria - Ademola Michael Akinsorotan; Adams Ovie Iyiola; Femi Peters Omotosho; Oyindamola Oluwaseun Adejayi; Fatimah Akorede Adesoye (Aceh Journal of Animal Science, 2023)
Heavy metals were determined in samples of fish tissues, soil, and water from nine randomly selected fish farms based on production facility (earthen pond) in the Ekiti Central (EC), Ekiti North (EN) and Ekiti South (ES) senatorial districts of Ekiti state. Fresh fish samples were collected and tissues from the dorsal area were used for analysis. Soil samples were collected using a soil auger, air-dried and stored in a sterile and well-labeled polythene bag. The water samples were collected using sterile bottles (2L) and labeled. After digestion of samples, Cadmium (Cd), Copper (Co), Chromium (Ch), Lead (Pb) and Zinc (Zn) were analyzed using Atomic Absorption Spectrometer (AAS). The levels of Co, Cd and Pb which are disastrous to fish species were observed to be elevated while Zn and Cu were observed to accumulate in the fish tissues. It was revealed that the heavy metals concentration across the districts was higher when compared with recommended standards. This suggests a dire need for intervention in controlling water pollution which is posed by anthropogenic activities in the state. It is recommended that there should be a reduction in the use of chemicals with high concentrations of heavy metals which is a significant source of pollution in the environment.